Sustainable Process Integration and Intensification : Saving Energy, Water and Resources - Manan, Zainuddin Abdul; Varbanov, Petar Sabev; Wan Alwi, Sharifah Rafidah (De Gruyter Textbook, 2018)
In its second edition, Sustainable Process Integration and Intensification continues the presentation of fundamentals of key areas of both fields. Thoroughly updated and extended to include the latest developments, the reader also finds illustrated working sessions for deeper understanding of the taught materials.The book is addressed to graduate students as well as professionals to help the effectively application in plant design and operation.